2016
DOI: 10.1371/journal.pone.0162061
|View full text |Cite
|
Sign up to set email alerts
|

The Occupational Risk of Influenza A (H1N1) Infection among Healthcare Personnel during the 2009 Pandemic: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: IntroductionThe aim of this review was to record systematically and assess the published literature relating to the occupational risk of influenza A (H1N1) infection among healthcare personnel during the 2009 pandemic.MethodsThe literature search was performed in June 2015. An update was carried out in May 2016. It was applied to the electronic databases EMBASE, MEDLINE, PsycINFO, PubMed, CINAHL and Google Scholar. The quality assessment was conducted with a tool using eight criteria. A meta-analysis was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 47 publications
1
64
0
9
Order By: Relevance
“…HCPs were significantly more likely to develop infection (odds ratio [OR] 2.08, 95% CI 1.73-2.51) with a pooled prevalence of 6.3%. 52 As COVID-19 has disproportionately affected HCPs, emergency physicians must be vigilant about potential exposure risks and adhere to appropriate infection prevention precautions. 53,54 In Italy, anywhere from 8-30%…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…HCPs were significantly more likely to develop infection (odds ratio [OR] 2.08, 95% CI 1.73-2.51) with a pooled prevalence of 6.3%. 52 As COVID-19 has disproportionately affected HCPs, emergency physicians must be vigilant about potential exposure risks and adhere to appropriate infection prevention precautions. 53,54 In Italy, anywhere from 8-30%…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Taken together, these studies highlight that setting [88] , occupation [89] or patient contact level, risk procedure [90] , circulating virus, and existing immunity in the population (i.e. H1N1) can all vary risk [63] . However, respiratory illness has been reported as one of the main causes of sickness absence in HWs [92] , [91] , pandemics and epidemics can be associated with concurrent increased rates of HW absenteeism [12] , [92] , [93] , and HWs do overall appear to be at risk of contracting influenza.…”
Section: Discussionmentioning
confidence: 88%
“…The review included a higher level systematic review and meta -analysis on the occupational risk of pandemic H1N1 in HWs compared to the general population or across occupations. This meta -analysis [63] evaluated 15 studies (29,358 subjects), including 11 high quality studies of laboratory-confirmed influenza, and showed a significantly increased OR = 2.08 (95% CI, 1.73–2.51) in HWs with a higher risk in physicians {OR = 6.03 (95% CI, 2.11–17.8)}.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational hazards are a good example. Health-care personnel are at increased risk of exposure to IAV as was shown during the 2009 A/H1N1 pandemic (Lietz et al 2016). Individuals who work in close contact with animals, such as birds and swine, may also have an increased risk of zoonotic transmission (Harris et al 2017;Root et al 2017).…”
Section: Additional Considerationsmentioning
confidence: 99%